2011
DOI: 10.3928/01913913-20100318-02
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Curvature and Thickness Development in Premature Infants

Abstract: In light of the few data available in the literature, these data provide more certainty about the CCT values of premature infants. The importance of CCT and CC fast variations after premature birth concerns both the knowledge of anterior segment development and the correct evaluation of IOP in immature eyes; the influence of these two parameters on the methods of IOP evaluation could be more remarkable at the lowest PCAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
3
12
0
Order By: Relevance
“…Previous studies have shown that the CCT in full-term newborns and premature infants is significantly thicker than in adults (Autzen & Bjornstrom 1989DeSilva et al 2011). Ultrasonic pachymetry did show that the CCT of premature babies decreases significantly to the same level previously reported in fullterm newborns at 3 months of age (Autzen & Bjornstrom 1991;Kirwan et al 2005).…”
Section: Central Corneal Thickness In Fullterm Saudi Newbornssupporting
confidence: 74%
“…Previous studies have shown that the CCT in full-term newborns and premature infants is significantly thicker than in adults (Autzen & Bjornstrom 1989DeSilva et al 2011). Ultrasonic pachymetry did show that the CCT of premature babies decreases significantly to the same level previously reported in fullterm newborns at 3 months of age (Autzen & Bjornstrom 1991;Kirwan et al 2005).…”
Section: Central Corneal Thickness In Fullterm Saudi Newbornssupporting
confidence: 74%
“…[1234] A progressive reduction in the intraocular pressure (IOP) of premature infants has been reported, also. [15] The purpose of this study was to evaluate the CCP and IOP differences in between premature and full-term newborns.…”
mentioning
confidence: 99%
“…Kirwan [19] studied 35 premature infants and found the CCT was 691 ± 87, 648 ± 72, 605 ± 59 and 564 ± 34 µm at 30-32, 34-35, 37-38, and 39-41 weeks of PA, respectively. De Silva [20] showed a gradual decrease in the CCT from 794 ± 34 µm at 28 weeks of PA to 559 ± 13 µm at 42 weeks of PA. CCT gradually thinned with the increase of PA.…”
Section: Discussionmentioning
confidence: 93%